Integrating Deep Learning-Based STEM Education to Enhance 21st-Century Skills among Generation Z - Mahyuna; Nurul Fajri Saminan; Deviyani Rusdiyanti Putri (Jurnal Serambi Ilmu, 2025)
The demands of 21st-century education emphasize the mastery of critical thinking, creativity, communication, collaboration, and digital literacy, particularly for Generation Z, who grew up in the era of rapid technological advancement. One relevant approach is the integration of Science, Technology, Engineering, and Mathematics (STEM) education with deep learning, which focuses on conceptual understanding, reflection, and active student engagement. This article aims to review recent national and international research findings on the implementation of deep learning-based STEM integration to enhance 21st-century skills among Generation Z. The study employs a literature review method by analyzing scientific publications from accredited national and international journals. The analysis reveals that integrating STEM with deep learning effectively strengthens science process skills, problem-solving abilities, collaboration, and digital literacy, aligning with the adaptive nature of Generation Z toward technological development. Furthermore, this approach promotes contextual, innovative, and future-oriented learning. Therefore, the integration of deep learning-based STEM education can be considered an effective strategy to facilitate the mastery of 21st-century skills while preparing Generation Z to face global challenges